2022
DOI: 10.3389/fsufs.2022.860780
|View full text |Cite
|
Sign up to set email alerts
|

Can Digitalization Levels Affect Agricultural Total Factor Productivity? Evidence From China

Abstract: The agricultural sector faces a food crisis and major challenges in green and sustainable development, and digital technology is an important countermeasure. In this paper, “digital technology” is used as a keyword to construct a regional digitalization level indicator. China's provincial panel data from 2013 to 2020 are adopted as samples to explore the impact of regional digitalization levels on agricultural total factor productivity and its mechanism. The study found the following: (1) Regional digitalizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…In this study, we examined whether and how dialect diversity affects the TFP of listed companies from the perspective of psychological distance. Unlike previous studies, we investigated the effect of informal institutions such as dialect diversity on TFP (e.g., Feng et al, 2021;Fu and Zhang, 2022;Wang et al, 2022). Using all Chinese-listed firms from 2007 to 2019, we found that dialect diversity significantly inhibits a firm's TFP.…”
Section: Discussionmentioning
confidence: 93%
“…In this study, we examined whether and how dialect diversity affects the TFP of listed companies from the perspective of psychological distance. Unlike previous studies, we investigated the effect of informal institutions such as dialect diversity on TFP (e.g., Feng et al, 2021;Fu and Zhang, 2022;Wang et al, 2022). Using all Chinese-listed firms from 2007 to 2019, we found that dialect diversity significantly inhibits a firm's TFP.…”
Section: Discussionmentioning
confidence: 93%
“…The digitization of agriculture encompasses the fusion of digital innovations like artificial intelligence, Big Data, and robotics, and these digital advancements are linked to agricultural production setups via the Internet of Things [31,67,105]. Within this evolving landscape, it is crucial to underscore that digitalization is not solely an escalating pattern but also an imperative for agriculture in the 21st century.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, it is clear that the promotion of Internet technologies and the development of rural e-commerce will inevitably promote changes in production by farmers, namely the use of green technologies in agriculture. On the one hand, the combination of e-commerce and the digital economy completes the construction of a digital system for the agricultural industry which is more conducive to the value-added and market demand transfer of green agricultural products and allows for more convenient mining and teaching of green agricultural technologies (Fu and Zhang 2022). On the other hand, the expansion of agricultural product sales by e-commerce and logistics platforms has led to a surge in the number of end customers with green consumption needs.…”
Section: Theories and Hypothesismentioning
confidence: 99%